Hotspots and Trends in Social-Emotional Learning Research in China: A Visual Analysis Based on CiteSpace - Menghe, Sarentonglaga; Deleg, Amartuvshin (Lavai - International Journal of Education, 2025)
Based on the CiteSpace visualization analysis method, this study systematically examines the research status, key issues, and development trends in the field of social-emotional learning (SEL) in China from 2012 to 2024. The study finds that SEL research in China has showen a trend of continuous growth and has gradually expanded to different school-age groups, including primary school students, preschool children, adolescents, and middle school students. The research hotspots mainly focus on topics such as emotional intelligence, school bullying, and teacher-student relationships, reflecting the important role of SEL in improving students’ mental health and promoting positive social behavior. In addition, this study reveals the current situation of cooperation among SEL research teams in China and finds that there is limited cross-regional and cross-institutional academic cooperation. Through quantitative analysis of the evolution of SEL research in China, this study provides a systematic review and offers valuable references for scholars, educational practitioners, and policy makers to promote the localization of SEL in China. In the future, further strengthening academic cooperation, optimizing the SEL curriculum system, and combining successful international experiences will help improve the effectiveness of SEL in China's education system and promote students’ all-round development and social adaptability.